Preserving ester-linked modifications reveals glutamate and aspartate mono-ADP-ribosylation by PARP1 and its reversal by PARG - Edoardo José Longarini; Ivan Matić (Nature Communications, 2024)
Abstract Ester-linked post-translational modifications, including serine and threonine ubiquitination, have gained recognition as important cellular signals. However, their detection remains a significant challenge due to the chemical lability of the ester bond. This is the case even for long-known modifications, such as ADP-ribosylation on aspartate and glutamate, whose role in PARP1 signaling has recently been questioned. Here, we present easily implementable methods for preserving ester-linked modifications. When combined with a specific and sensitive modular antibody and mass spectrometry, these approaches reveal DNA damage-induced aspartate/glutamate mono-ADP-ribosylation. This previously elusive signal represents an initial wave of PARP1 signaling, contrasting with the more enduring nature of serine mono-ADP-ribosylation. Unexpectedly, we show that the poly-ADP-ribose hydrolase PARG is capable of reversing ester-linked mono-ADP-ribosylation in cells. Our methodology enables broad investigations of various ADP-ribosylation writers and, as illustrated here for noncanonical ubiquitination, it paves the way for exploring other emerging ester-linked modifications.